2017
DOI: 10.1111/ijmr.12156
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review on Recent Lean Research: State‐of‐the‐art and Future Directions

Abstract: Lean management (LM) has attracted the interest of scientists and practitioners since 1990, when Womack et al. (Womack, J.P., Jones, D.T. and Roos, D. (1990). The Machine that Changed the World. New York, NY: Rawson Associates) popularized the Japanese manufacturing approach aimed at eliminating waste to improve operational performance and customer satisfaction. Over the years, the lean concept has evolved becoming a managerial paradigm applicable to different sectors and processes with impressive results. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
214
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 245 publications
(252 citation statements)
references
References 185 publications
(249 reference statements)
5
214
0
6
Order By: Relevance
“…The most recent systematic reviews on lean thinking are about the service sector (including banking/finance, the public sector, and education). 46 To the best of the authors' knowledge, no literature reviews have been published on the use of LM in agricultural production chains. Consequently, a review of uses of lean thinking in agriculture and agri-chains may make a significant important contribution toward these systems, helping to support efficiency-oriented redesign to seek both operational efficiency 47 and performance improvements.…”
Section: Background and Positioning Of This Paper Key Aspects Of Agrimentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent systematic reviews on lean thinking are about the service sector (including banking/finance, the public sector, and education). 46 To the best of the authors' knowledge, no literature reviews have been published on the use of LM in agricultural production chains. Consequently, a review of uses of lean thinking in agriculture and agri-chains may make a significant important contribution toward these systems, helping to support efficiency-oriented redesign to seek both operational efficiency 47 and performance improvements.…”
Section: Background and Positioning Of This Paper Key Aspects Of Agrimentioning
confidence: 99%
“…A bibliographical search was conducted on investigations of agricultural supply chains, and it was found that no significant literature reviews had been done on LM developments in agricultural production. The most recent systematic reviews on lean thinking are about the service sector (including banking/finance, the public sector, and education) …”
Section: Introductionmentioning
confidence: 99%
“…The study revealed an insufficiency of existing management systems and practices at successfully dealing with issues that occur in the social sustainability pillar. Fortunately, Danese et al, (2017) conducted an SLR on recent lean research and its future direction [130]. The authors identified relationships of lean-green, and lean-social sustainability among issues to be tackled in the future research studies.…”
Section: Past Literature Reviewsmentioning
confidence: 99%
“…The applicability of both lean and sustainability is quite extensive and expandable. Several past studies concluded that both concepts are relevant for, and versatile enough to, accommodate needs of any industry [8,88,130,171,172]. Evidence of both separate [28] and co-deployment [173] of frameworks were prominent in the literature since early 1990s and early 2000s, respectively.…”
Section: Versatility Organizational Culture and Deployment Plan Conmentioning
confidence: 99%
See 1 more Smart Citation